A Retrospective Study Of Breast Augmentation In Transgender Women : Outcome, Complications, Patient Satisfaction. - Raj. M, Mohan; M.S, Gabriel Ernest; MS. M.Ch, V.L. Aishwarya; .S, M.S, Dharmarajan; M.S, M. Ramula; Ashiq.A, Ashiq.A (Journal of Neonatal Surgery, 2025)
Background Breast augmentation is a crucial component of gender-affirming surgery for many transgender women. However, limited data exist on postoperative recovery, complication rates, and satisfaction in this population. This retrospective study compares outcomes between sub glandular and sub pectoral implant placements in transgender women. Objectives To compare postoperative pain, recovery time, and complication rates between sub-glandular and sub-pectoral breast augmentation in transgender women. To assess patient satisfaction across both surgical approaches. To identify factors influencing postoperative complications and satisfaction. Methods: A total of 98 transgender women who underwent primary breast augmentation between 2023 and 2025 were retrospectively reviewed. Patients were divided into two groups based on implant location: sub glandular (Group A) and sub pectoral (Group B). Parameters evaluated included operative data, postoperative recovery, complications, and satisfaction. Results: Group A (n=41) and Group B (n=57) showed similar demographic profiles. Group A had significantly less postoperative pain duration (mean 49.2 h vs. 68.5 h), and shorter drain use (1.8 vs. 3.0 days). Nipple-areola numbness was more common in Group A (9.7%). Capsular contracture and displacement were slightly more prevalent in Group B, though not statistically significant. Overall satisfaction was high in both groups (82.9% in Group A vs. 78.9% in Group B rated satisfaction ≥4 on a 5-point scale). Conclusion: Sub glandular placement may offer faster recovery and less postoperative discomfort, while sub pectoral placement could reduce the risk of visible implant edges in thinner patients. Satisfaction was influenced primarily by complications like contracture and displacement, not implant plane.